Gesang des Lebens : das Werk Frans Masereels - Hagelstange, Rudolf; Hesse, Hermann; Mann, Thomas; Verhaeren, Emile; Whitman, Walt; Zweig, Stefan (Hannover: Fackelträger Verlag, 1957)
"Rudolf Hagelstange ; mit Beiträge von Hermann Hesse, Thomas Mann, Emile Verhaeren...et al."